Effects of Acute and Chronic Administration of Agomelatine on Oxidative Stress Parameters in Mice - Canpolat, Sinan; Bulmus, Funda Gulcu; Bulmus, Ozgur; Kacar, Emine; Serhatlioglu, Ihsan; Ozcan, Mete (Wiley, 2017)
[Abstract Not Available]